Weighed Altruism: The Construction of Identity and Hidden Motivations in the World of Elite Philanthropy - Zainal, Mohammad; Nor Paizin, Mohsin (Asian Journal of Muslim Philanthropy and Citizen Engagement, 2026)
This study aims to deconstruct the concept of “weighed altruism”, a form of negotiated generosity in elite philanthropy where moral claims, strategic interests, and power dynamics are perpetually balanced. Employing a qualitative critical literature review, it synthesizes scholarly discourse, media narratives, and theoretical frameworks from the past two decades, utilizing thematic analysis and theoretical triangulation to examine the performative, motivational, and representational layers of philanthropic practice. The analysis reveals that philanthropic acts by elites are rarely disinterested; they serve as instruments for moral legitimization, corporate reputation management, network expansion, and power consolidation, while simultaneously reproducing structural inequalities, depoliticizing social justice issues, and fostering public skepticism. Against the backdrop of widening socio-economic disparities and increased scrutiny of elite actors, philanthropy has evolved from simple charity to a complex social performance that intertwines virtue with calculation, converting economic capital into symbolic capital within competitive social arenas. The study concludes that elite philanthropy embodies a profound ambivalence, operating as a dual-edged mechanism that channels resources toward public good yet reinforces the very hierarchies it purports to address. Consequently, a paradigm shift is needed in philanthropic studies toward more critical, interdisciplinary, and power-conscious engagements, urging future research to explore transformative philanthropic models that prioritize equity and structural change over symbolic legitimization.